2023
DOI: 10.1097/qai.0000000000003183
|View full text |Cite
|
Sign up to set email alerts
|

Food and Water Insecurity in Sexual and Gender Minority Groups Living With HIV in Lagos, Nigeria

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…There is very little research explicitly linking sexual identities and water insecurity experiences. One exception is Hamill et al (2023), who studied water and food insecurity among sexual and gender minority people living with HIV in Lagos, Nigeria. Same‐sex sexual activity and relationships, dressing in accordance with a gender not assigned at birth, and transgender activism are illegal in Nigeria, with severe penalties particularly in northern states under Sharia law (Gaudio, 2009; Ogueji & Ogueji, 2022; Sekoni et al, 2020).…”
Section: Gender Concepts For Water Insecurity Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…There is very little research explicitly linking sexual identities and water insecurity experiences. One exception is Hamill et al (2023), who studied water and food insecurity among sexual and gender minority people living with HIV in Lagos, Nigeria. Same‐sex sexual activity and relationships, dressing in accordance with a gender not assigned at birth, and transgender activism are illegal in Nigeria, with severe penalties particularly in northern states under Sharia law (Gaudio, 2009; Ogueji & Ogueji, 2022; Sekoni et al, 2020).…”
Section: Gender Concepts For Water Insecurity Researchmentioning
confidence: 99%
“…Same‐sex sexual activity and relationships, dressing in accordance with a gender not assigned at birth, and transgender activism are illegal in Nigeria, with severe penalties particularly in northern states under Sharia law (Gaudio, 2009; Ogueji & Ogueji, 2022; Sekoni et al, 2020). In research with 357 respondents—including 74% men who have sex with men, 18% transgender women, and 8% who identify outside binary gender categories—Hamill et al (2023) found at baseline that 32% experienced water insecurity. Regardless of gender identity, respondents were more likely to experience water insecurity when they were co‐habiting with a man, engaged in transactional sex, older, or food insecure.…”
Section: Gender Concepts For Water Insecurity Researchmentioning
confidence: 99%
“…Thus, a better understanding water insecurity experiences among LGBTQ populations is urgently needed (Brewis et al, 2023 ). For instance, a Nigerian study with LGBTQ persons found water insecurity was associated with living with a man, transactional sex and food insecurity (Hamill et al, 2023 ), and Brewis et al describe how this study “highlights the intersectional nature of gender and sexual identities in creating risks for water insecurity” (p. 6) (Brewis et al, 2023 ). The limited research that has considered LGBTQ persons in relation to WASH is focused on sanitation, in particular, access to toilets among transgender persons (Benjamin and Hueso, 2017 ; Boyce et al, 2018 ; Moreira et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%